Artificial Intelligence Regulation and Political Ethics: An Analysis of Indonesia's Position in AI Governance - Feri Nugroho (Politeknik Siber Cerdika Internasional, 2025)
The rapid development of artificial intelligence (AI) technology is having far-reaching impacts on global economic, social and political aspects. However, the absence of universal ethical standards and regulatory gaps between developed and developing countries have posed serious challenges to fair and inclusive AI governance. Indonesia as the largest democracy in Southeast Asia is faced with a dilemma: responding to AI opportunities while ensuring ethical sustainability and digital sovereignty. This research aims to analyze Indonesia's normative and practical position in the dynamics of global AI governance, focusing on the regulatory dimension, political ethics, and participation in multilateral forums such as the G20, UNESCO, and ASEAN. A qualitative approach was used with methods of public policy analysis, official document studies (Personal Data Protection Bill, National AI Strategy), and interviews with technology experts and digital diplomats. The results show that Indonesia is still at an early stage in building a comprehensive AI regulatory framework, although it has shown commitment through strengthening its data privacy policy and national AI strategy. However, the absence of AI-specific laws and the lack of active engagement in global ethical governance frameworks are major obstacles in strengthening Indonesia's position as a normative actor at the international level.